2007
DOI: 10.1562/0031-8655(2001)0740064potbcs2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamics of the Bacteriochlorophyll-Carotenoid System. 1. Bacteriochlorophyll-photosensitized Oxygenation of β-Carotene in Acetone¶

Abstract: Carotenoids are well-known physical quenchers of chlorophyll excited states and reactive oxygen species both in vivo and in vitro. They may also be involved in chemical quenching undergoing, e.g. isomerizations or oxidations. We have found that ␤-carotene (Car) in aerobic acetone is rapidly oxygenated under strong illumination with red light ( exc Ն 630 nm) in the presence of bacteriopheophytin a. At the same time the photosensitizer undergoes only slight (Ͻ10%) photodegradation. By preparative high-performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
(65 reference statements)
2
17
0
3
Order By: Relevance
“…For b-carotene and lutein, the accumulation of the endoperoxide (m/z 569 and 602, respectively) occurred during the first 15 min of illumination and then declined. A similar transitory accumulation of b-carotene endoperoxide was reported for bacteriochlorophyll-photosensitized oxidation of b-carotene in vitro (Fiedor et al, 2001). In Figure 1.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…For b-carotene and lutein, the accumulation of the endoperoxide (m/z 569 and 602, respectively) occurred during the first 15 min of illumination and then declined. A similar transitory accumulation of b-carotene endoperoxide was reported for bacteriochlorophyll-photosensitized oxidation of b-carotene in vitro (Fiedor et al, 2001). In Figure 1.…”
Section: Resultssupporting
confidence: 76%
“…High-light stress induced an increase in the b-carotene endoperoxide levels, but this effect was not more pronounced in the cat2 mutant compared with the wild type, confirming that this compound is specific to 1 O 2 attack on b-carotene. This study has identified a rather large range of products generated during the in vitro oxidation of b-carotene and xanthophylls by 1 O 2 , thus extending previous studies (Stratton et al, 1993;Yamauchi et al, 1998;Fiedor et al, 2001;Montenegro et al, 2002). More precisely, the presented results confirm the formation of an endoperoxide that appears to be a major oxidation product for both b-carotene and xanthophylls.…”
Section: B-carotene Endoperoxide In Arabidopsis Mutantssupporting
confidence: 86%
See 2 more Smart Citations
“…Only in the last decade or so, since the characterization of several intermediate catabolites of Chl accompanied by advances in molecular biology methods for identifying the enzymes involved, has the process appeared less enigmatic (Gossauer and Engel, 1996;Hörtensteiner, 1999;Kräutler and Matile, 1999;Matile, 2000;Oberhuber et al, 2003;Kräutler and Hörtensteiner, 2006;Kräutler, 2008). Now it is seen as a sequence of well-synchronized steps in the safe withdrawal of Chl molecules, which, once released from photosynthetic complexes, become photocytotoxic due to the photodynamic effect (Fiedor et al, 1993(Fiedor et al, , 2001. The withdrawal of Chls also seems correlated with other processes of salvaging thylakoid proteins and lipids (Ischebeck et al, 2006).…”
mentioning
confidence: 99%